Phase reconstruction via metasurface-integrated quantum analog operation - Qiuying Li; Minggui Liang; Shuoqing Liu; Jiawei Liu; Shizhen Chen; Shuangchun Wen; Hailu Luo (Opto-Electronic Advances, 2025)
Phase reconstruction plays a pivotal role in biology, medical imaging, and wavefront sensing. However, multiple measurements and adjustments are usually required for conventional schemes, which inevitably reduces the quality of phase imaging. Here, based on multi-channel metasurface and quantum entanglement source, a simple and integrated quantum analog operation system is proposed to realize quantitative phase reconstruction with a high signal-to-noise ratio (SNR) under a low signal photon level. Without additional measurements and adjustments, four differential images necessary for the phase reconstruction are captured simultaneously. The non-local correlation of entangled photon pairs enables to remotely manipulate working modes of the system. Besides, the consistency of entangled photon pairs in time domain makes it possible to achieve a high SNR imaging by trigger detection. The results may potentially empower the application of metasurfaces in optical chip, wave function reconstruction, and label-free biology imaging.